Models of Research Collaboration to Support the Self-Reliance of Indonesia’s Pharmaceutical Industry - Brian Pratistha; Evi Sylvia Nurrasjid; Amin Nurhuda; Endang Sulastri; Muniha Hikmah; Ahmad Syafiq Kamil (Pusbindiklatren Bappenas, 2026)
Promoting a self-reliant pharmaceutical industry constitutes one of the national strategic agendas. The government undertakes efforts toward self-sufficiency to strengthen health resilience and advance Indonesia’s economic transformation. This policy paper aims to formulate an integrated research collaboration model designed to enhance research and development capacity, increase domestic production capability, and reduce dependence on imported pharmaceutical raw materials and products. The research methodology encompasses an analysis of relevant policies and regulations, a comparative study of three countries considered to have more advanced pharmaceutical sectors, and a mapping of key actors and interaction mechanisms within the pharmaceutical research and innovation ecosystem. The problem identification findings indicate that current challenges include limited inter-institutional coordination, weak technology transfer mechanisms, and the suboptimal alignment between research funding and incentives with industry needs. This policy paper further finds that a primary prerequisite for mission-oriented research collaboration is the presence of a jointly agreed strategic vision among stakeholders, supported by collaborative funding schemes and adaptive intellectual property governance arrangements. The resulting policy recommendations emphasize the need to strengthen the role of the state as an orchestrator of collaboration and to ensure closer integration between research initiatives and pharmaceutical industrialization policies.